2021
DOI: 10.1177/0963689720985113
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Inhibits the Proliferation, Migration, and Stem-like Properties of Bladder Cancer Mainly by Suppressing the Hedgehog Pathway

Abstract: Bladder cancer is one of the most common malignancies. The existence of bladder cancer stem cells (BCSCs) has been suggested to underlie bladder tumor initiation and recurrence. Propofol is a commonly used intravenous anesthetic. Here, we find that propofol can dramatically block the activation of Hedgehog pathway in BCSCs. The propofol strongly repressed the growth of cancer cells. Attenuated proliferation and enhanced apoptosis of tumor cells were observed upon propofol stimulation. Furthermore, propofol red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…17 Several mechanisms by which propofol specifically exerts antitumor effects on bladder cancer have also been presented. [6][7][8][9][10] In addition, meta-analyses indicate a survival benefit with propofol-based anesthesia for various cancers. [18][19][20][21] Please note that the 5-yr survival rates were calculated using the Kaplan-Meier approach, adjusting for the patients that were censored during follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Several mechanisms by which propofol specifically exerts antitumor effects on bladder cancer have also been presented. [6][7][8][9][10] In addition, meta-analyses indicate a survival benefit with propofol-based anesthesia for various cancers. [18][19][20][21] Please note that the 5-yr survival rates were calculated using the Kaplan-Meier approach, adjusting for the patients that were censored during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…4 Finally, a randomized, controlled trial comparing the combination of propofol and paravertebral block with sevoflurane and opioids showed noninferiority in cancer recurrence between the two groups. 5 However, specific to bladder cancer, a few in vitro studies [6][7][8][9] and one clinical study 10 indicate that propofol interferes positively with the immune system against bladder cancer by regulation of several different microRNA pathways and the Hedgehog pathway. However, it is unclear whether these proposed advantages really translate to better survival.…”
mentioning
confidence: 99%
“…20,26,27 Besides, contradictory effects of propofol on cell apoptosis and regeneration ability have been reported. [28][29][30] This study, for the first time, investigated the effect of propofol on corneal activated keratocytes for inflammation, fibrogenesis, and apoptosis. We showed that propofol treatment could significantly decrease the expression level of IL-1b in CAKs treated with 0.5 and 5 mM propofol.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria are as follows: (1) all the included patients met the corresponding criteria for bladder cancer resection [ 8 ], (2) aged between 18 and 85 years, and (3) the clinical data of all included patients were complete.…”
Section: Methodsmentioning
confidence: 99%